Temperatures and Mg/Ca ratios of sediment core SO189/2_039KL - Mahyar Mohtadi; Matthias Prange; Enno Schefuß; Tim C Jennerjahn (PANGAEA, 2024)
Mg/Ca and Mg/Ca-derived SST and TWT estimates of sediment core SO189/2_039KL. For Mg/Ca analyses, samples were cleaned following a slightly modified protocol of Barker et al (2003). Mg/Ca ratios were measured with an Agilent Technologies 700 Series ICP-OES with a CETAX ASX-520 auto sample at the Faculty of Geosciences, University of Bremen. Mg/Ca ratios were converted to temperature using the multispecies Mg/Ca-temperature calibration of Anand et al. (2003; doi:10.1029/2002PA000846) for G. ruber and the species-specific Mg/Ca-temperature calibration of Anand et al. (2003; doi:10.1029/2002PA000846) for P. obliquiloculata.
In: Mohtadi, M et al. (2017): Hydroclimate proxy data from the eastern tropical Indian Ocean [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.877994